2021
DOI: 10.1038/s41598-021-97855-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hyperammonia and altered concentrations of urea cycle metabolites in a 5-day swine experiment of sepsis

Abstract: We measured plasma and cerebrospinal fluid (CSF) metabolite concentrations in a 5-day porcine sepsis model of fecal peritonitis. The objectives were: (i) to verify whether the expected pathways that had emerged in previous studies pertain only to the early inflammatory response or persist for the subsequent days; (ii) to identify metabolic derangements that arise later; (iii) to verify whether CSF metabolite concentrations were altered and if these alterations were similar to those in the blood or delayed. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…At the end of the experiment animals were euthanized by bolus infusion of 40 mmol of potassium chloride. Further details can be found in 26 .…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment animals were euthanized by bolus infusion of 40 mmol of potassium chloride. Further details can be found in 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Effects of small increases in central venous pressure on hepatic arterial perfusion and hepatic oxygen consumption, and alterations in metabolic pathways suggested from plasma and cerebrospinal fluid samples have been reported previously [31,32] . Here we report data about the effects of repeated, acute reductions in hepatic DO 2 by portal vein occlusion on hepatic oxygen extraction capability and effects of sepsis on the HABR during prolonged resuscitation.…”
Section: Methodsmentioning
confidence: 74%
“…Systemic hemodynamics of the animals over time have been described previously [31,32] . Briefly, sepsis was associated with hyperthermia, hypotension, tachycardia and an increase in arterial lactate concentration.…”
Section: Evolution Of Signs Of Sepsis and Administered Treatmentmentioning
confidence: 99%
“…In these cohorts, 100% of control mice and ~93% of CLP/DCS mice survived to the experimental endpoint of 27/28 days (Figure 1A) or in combined studies assessing acute survival, 100% control mice and ~82% of CLP/DCS mice (Figure S1A). To longitudinally monitor sepsis progression in our model, we measured serum levels of CRP (a marker of inflammation found to be increased in both mouse and human sepsis studies), 33,34 and AST activity, an indicator of liver dysfunction found to be increased in both mouse and pig models of sepsis 25,33,35 (Figure 1B). Both CRP and AST were increased at CLP/DCS Day 4 (+67.90 ± 10.97% and +95.59 ± 28.66%, respectively).…”
Section: Utilization Of Cecal Ligation and Puncture And Daily Chronic...mentioning
confidence: 99%